Effect of flooring on growth performance, behaviour, health and economics in Surti buffalo calves during winter - SORATHIYA, L M; RAVAL, A P; KHARADI, V B; TYAGI, K K; PATEL, M D (The Indian Journal of Animal Sciences, 2019)
Surti buffalo calves (25) of an average 63.52±6.01 days age and 49.68±2.16 Kg weight were randomly divided into 5 homogeneous treatment group of floor types, viz. Concrete floor (CC), Kachcha soil floor without bedding (SOIL), Concrete floor with paddy straw bedding (CC+PS), Kachcha soil floor with paddy straw bedding (SOIL+PS) and Rubber mat bedding (RM) as per Latin Square Design (LSD) for 60 days. DM intake and body weight were recorded at fortnightly interval. The behavioural parameters of the calves were studied by four instantaneous observations for three days in a week. Faecal consistency scoring and eye scoring was recorded as per standard method. Average daily gain (ADG) was highest in SOIL+PS (424.00 g) and lowest in CC (294.80 g). The pooled concentrate, roughage, milk and total DMI was 0.93±0.04, 0.92±0.05, 0.22±0.01 and 2.07±0.07 kg/day, respectively. Highest concentrate intake was in CC group whereas lowest was in SOIL group. Roughage intake was higher in SOIL+PS and CC+PS in which paddy straw was used. Behavioural parameters like cross grooming, licking of floor, playfulness by running/fighting and smelling were statistically (P